Perlindungan Korban Kekerasan Dalam Rumah Tangga Dalam Hukum Pidana Indonesia - La Jamaa (Jurnal Cita Hukum, 2014)
Abstract: The protection of Domestic Violence Victims in the Indonesian Criminal Law. The existence of the Law No. 23 Year 2004 on the Elimination of Domestic Violence are expected to provide legal protection for victims of domestic violence (KDRT) significantly. The form of protection regulated in this Act is the temporary protection of the police, the courts and the protection of victims in the placement of "safe houses". However, research results through both District Court and informants, suggests that a form of protection of domestic violence victims are still dominant through repressive measures (sentence of imprisonment) to the perpetrators, while the protection of temporary and permanent protection of the court was unnoticed. Abstrak: Perlindungan Korban Kekerasan dalam Rumah Tangga dalam Hukum Pidana Indonesia. Keberadaan Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan dalam Rumah Tangga diharapkan mampu memberikan perlindungan hukum bagi korban Kekerasan Dalam Rumah Tangga (KDRT) secara signifikan. Bentuk perlindungan yang diatur dalam Undang-undang ini adalah perlindungan sementara dari kepolisian, perlindungan pengadilan serta penempatan korban di “rumah aman”. Namun hasil penelitian baik melalui putusan Pengadilan Negeri maupun informan, menunjukkan bahwa bentuk perlindungan korban KDRT masih dominan melalui tindakan represif (hukuman pidana penjara) kepada pelaku, sedangkan perlindungan sementara dan perlindungan tetap dari pengadilan kurang diperhatikan DOI: 10.15408/jch.v1i2.1467